The Integration of Supervisory Control and Data Acquisition (SCADA) on the Crushing and Barge Loading Conveyor Systems - Sutrisno, Imam; Nurhidta, Ihza Anfasa Dua; Munadhif, Ii; Hidayat, Edy Prasetyo; Endrasmono, Joko; Priyonggo, Projek; Hartanto, Tri Mulyatno Budhi (International Journal of Marine Engineering Innovation and Research, 2025)
The utilization of the Crushing and Barge Loading Conveyor (BLC) systems is important in coal processing. A crushing system is required as a tool for the process of crushing coal into smaller sizes and then transferring it to the stockpile. While a BLC system is needed to transport coal from the stockpile to the barge. In general, the control and supervision systems for crushing and BLC systems are carried out separately by two operators. However, the distance between two operators causes a time lag information. In this research, we create a Supervisory Control and Data Acquisition (SCADA) system with the type of Multiple Programmable Logic Controller (PLC) on the Crushing and BLC systems using Profinet communication integrated by two PLCs with one Human Machine Interface (HMI) and WinCC. The system is equipped with real-time data, automatic control, and online surveillance with smartphones via the S7APP application. The error resulting from the reading of each component by the HMI and smartphone reaches 0%, while for automatic control, the system works very well, having a success rate of 100%.